Differences in long-term all-cause and cardiovascular mortality according to heart failure aetiology in ambulatory patients. (14th October 2021) - Spitaleri, G; Cediel, G; Santiago-Vacas, E; Codina, P; Domingo, M; Zamora, E; Santesmases, J; Diez-Quevedo, C; Troya, M; Boldo, M; Altimir, S; Alonso, N; et al.
Abstract: Background: Heart failure (HF) is the final stage of many cardiac disorders. Mortality in heart HF remains challenging despite improvement in outcomes proved in clinical trials in HF with reduced ejection fraction and it can be influenced by the aetiology of HF. Purpose: To assess differences in long-term mortality (up to 18 years) in a real-life cohort of HF outpatients according to the aetiology of HF. Methods: Consecutive patients with HF admitted at the HF Clinic from August 2001 to September 2019 were included. Follow-up was closed at 30.9.2020. HF aetiology was divided into ischemic heart disease (IHD), dilated cardiomyopathy (CM) –including non-compaction CM–, hypertensive CM, alcohol-derived CM, drug-derived CM, valvular disease, hypertrophic CM and others. For the present analysis, this latter group was excluded due to the big heterogeneity and limited number of patients in each subtype of aetiology. All-cause death and cardiovascular death were the primary end-points. Fine & Gray method for competing risk was used for cardiovascular mortality analysis. Results: Out of 2387 patients included (age 66.5±12.5 years, 71.3% men, LVEF 35.4%±14.2, mainly in NYHA class II [65.5%] and III [26.5%]), 1317 deaths were recorded (731 from cardiovascular cause) during a maximum follow-up of 18 years (median 4.1 years [IQR 2–7.8] for the total cohort, 5.3 years [IQR 2.6–9.7] for survivors). Figure 1 shows Cox regression multivariable analysis for all-cause death and cardiovascular mortality. Considering IHD aetiology as reference, only dilated CM showed significantly lower risk of all-cause death, and only drug-induced CM showed higher risk of all-cause death. However, when cardiovascular mortality was considered almost all aetiologies showed significant lower risk of cardiovascular death than IHD. Figure 2 shows adjusted survival curves (A) and adjusted incidence curves of cardiovascular death (B) based on HF aetiology. Conclusions: After adjusting for multiple prognostic factors among the studied HF aetiologies, dilated CM and drug-related CM showed the lowest and the highest risk of all-cause death, respectively. Patients with IHD showed the highest adjusted risk of cardiovascular death. Funding Acknowledgement: Type of funding sources: None.